(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article explores pedagogical strategies for developing students’ independent and critical thinking skills in the context of today’s intensive information flow. The primary objective of the study is to substantiate the effectiveness of the integrated use of Problem-Based Learning (PBL), Case-Based Learning (CBL), and strategic SWOT analysis within the educational process.